Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1017/s0031182001001056
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and cytochemical localization of an ATP diphosphohydrolase from Leishmania amazonensis promastigotes

Abstract: An ATP diphosphohydrolase was identified in the plasma membranes isolated from promastigote forms of Leishmania amazonensis. Both ATP and ADP were hydrolysed at similar rates by the enzyme. Other nucleotides such as UTP, GTP and CTP were also degraded, revealing a broad substrate specificity. Adding ATP and ADP simultaneously, the amount of hydrolysis achieved was compatible with the presence of a single enzyme. ATPase activity was not affected by addition of vanadate, ouabain, thapsigargin, dicyclohexylcarbod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 0 publications
1
35
0
1
Order By: Relevance
“…It has already been demonstrated that L. amazonensis promastigotes present an ecto-ATPase activity that correlates with the virulence of the strain (Berredo- Pinho et al 2001;Coimbra et al 2002). In view of this observation, we decided to compare the ability of metacyclic promastigotes from L. amazonensis and L. braziliensis to hydrolyze extracellular ATP and AMP.…”
Section: Extracellular Nucleotide Hydrolysismentioning
confidence: 99%
“…It has already been demonstrated that L. amazonensis promastigotes present an ecto-ATPase activity that correlates with the virulence of the strain (Berredo- Pinho et al 2001;Coimbra et al 2002). In view of this observation, we decided to compare the ability of metacyclic promastigotes from L. amazonensis and L. braziliensis to hydrolyze extracellular ATP and AMP.…”
Section: Extracellular Nucleotide Hydrolysismentioning
confidence: 99%
“…Rhodamine 123 (0.3 μg/mL) was added, and the cells were incubated for 10 min in the dark. The cells were washed twice in HBSS, and the fluorescence intensity was measured using a fluorimetric microplate reader, with excitation and emission wavelengths of 485 and 520 nm, respectively (Coimbra et al, 2002). Also, the internal controls were the same of the evaluation of ROS production and of the cellular membrane permeability.…”
Section: Activity On Mitochondrial Membrane Potentialmentioning
confidence: 99%
“…Potato apyrase was one of the first proteins of this family to be purified (Traverso-Cori et al 1965). Since then, a number of ATP diphosphohydrolases differing in their catalytic properties and subcellular localization have been identified from different species, such as parasites, mammals and plants, and play important roles in the control of nucleotides levels in a variety of physiological processes (Coimbra et al 2002, Gendron et al 2002, Ivanenkov et al 2005.Studies in our laboratory showed that potato apyrase purified from Solanum tuberosum presents remarkable im- (Vasconcelos et al 1996, Faria-Pinto et al 2004) and cellular immune responses in mice, inducing a mixed Th1/Th2-type cytokine secretion profile (unpublished data). Rabbit policlonal antibodies against purified potato apyrase showed strong cross-immunoreactivity with partially purified S. mansoni ATP diphosphydrolase isoforms, suggesting that the parasite and vegetable proteins share conserved epitopes (Vasconcelos et al 1996, Faria-Pinto et al 2004).…”
mentioning
confidence: 99%
“…Potato apyrase was one of the first proteins of this family to be purified (Traverso-Cori et al 1965). Since then, a number of ATP diphosphohydrolases differing in their catalytic properties and subcellular localization have been identified from different species, such as parasites, mammals and plants, and play important roles in the control of nucleotides levels in a variety of physiological processes (Coimbra et al 2002, Gendron et al 2002, Ivanenkov et al 2005.…”
mentioning
confidence: 99%